Microbially enhanced dissolution of HgS in an acid mine drainage system in the California Coast Range. Issue 1 (13th November 2013) - Jew, A. D.; Behrens, S. F.; Rytuba, J. J.; Kappler, A.; Spormann, A. M.; Brown, G. E.
Abstract Mercury sulfides (cinnabar and metacinnabar) are the main ores of Hg and are relatively stable under oxic conditions (Ksp = 10−54 and 10−52, respectively). However, until now their stability in the presence of micro‐organisms inhabiting acid mine drainage (AMD) systems was unknown. We tested the effects of the AMD microbial community from the inoperative Hg mine at New Idria, CA, present in sediments of an AMD settling pond adjacent to the main waste pile and in a microbial biofilm on the surface of this pond, on the solubility of crystalline HgS. A 16S rRNA gene clone library revealed that the AMD microbial community was dominated by Fe‐oxidizing (orders Ferritrophicales and Gallionellas) and S‐oxidizing bacteria (Thiomonas sp.), with smaller amounts (≤6%) being comprised of the orders Xanthomondales and Rhodospirillales. Though the order Ferritrophicales dominate the 16S rRNA clones (>60%), qPCR results of the microbial community indicate that the Thiomonas sp. represents ~55% of the total micro‐organisms in the top 1 cm of the AMD microbial community. Although supersaturated with respect to cinnabar and metacinnabar, microcosms inoculated with the AMD microbial community were capable of releasing significantly more Hg into solution compared to inactivated or abiotic controls. Four different Hg‐containing materials were tested for bacterially enhanced HgS dissolution: pure cinnabar, pure metacinnabar, mine tailings, and calcine material (processed ore). In the microcosm with metacinnabar, the presence of the AMD microbial community resulted in an increase of dissolved Hg concentrations up to 500 μg L‐1 during the first 30 days of incubation. In abiotic control microcosms, dissolved Hg concentrations did not increase above 100 ng L−1. When Hg concentrations were below 50 μg L‐1, the Fe‐oxidizing bacteria in the AMD microbial community were still capable of oxidizing Fe(II) to Fe(III) in the AMD solution, whereas concentrations above 50 μg L−1 resulted in inhibition of microbial iron oxidation. Our experiments show that the AMD microbial community contributes to the dissolution of mercury sulfide minerals. These findings have major implications for risk assessment and future management of inoperative Hg mines worldwide.